Dissent and authority in early modern Ireland : the English problem from Bale to Shakespeare - Wong, Jane Yeang Chui (New York : Routledge, Taylor & Francis Group, 2020)
Dissent and Authority in Early Modern Ireland: The English Problem from Bale to Shakespeare examines the problems that beset the Tudor administration of Ireland through a range of selected 16th century English narratives. This book is primarily concerned with the period between 1541 and 1603. This bracket provides a framework that charts early modern Irish history from the constitutional change of the island from lordship to kingdom to the end of the conquest in 1603. The mounting impetus to bring Ireland to a "complete" conquest during these years has, quite naturally, led critics to associate England's reform strategies with Irish Otherness. The preoccupation with this discourse of difference is also perceived as the "Irish Problem," a blanket term broadly used to describe just about every aspect of Irishness incompatible with the English imperialist ideologies. The term stresses everything that is "wrong" with the Irish nation--Ireland was a problem to be resolved. This book takes a different approach towards the "Irish Problem." Instead of rehashing the English government's complaints of the recalcitrant Irish and the long struggle to impose royal authority in Ireland, I posit that the "Irish Problem" was very much shaped and developed by a larger "English Problem," namely English dissent within the English government. The discussions in this book focuse on the ways in which English writers articulated their knowledge and anxieties of the "English Problem" in sixteenth-century literary and historical narratives. This book reappraises the limitations of the "Irish Problem," and argues that the crown's failure to control dissent within its own ranks was as detrimental to the conquest as the "Irish Problem," if not more so, and finally, it attempts to demonstrate how dissent translate into governance and conquest in early modern Ireland.
OCLC-licensed vendor bibliographic record.
Keywords: Dissenters -- Ireland; Authority; LITERARY CRITICISM / General